A steady-state computational investigation of the multiple anode attachments in a high-intensity argon arc. (25th June 2021) - Chen, Tang; Liao, Meng-ran; Sun, Su-rong; Wang, Hai-xing
Abstract: In this work a steady-state computational investigation of the multiple anode attachments phenomenon is performed for a high-intensity argon arc at atmospheric pressure. The simulation couples a three-dimensional arc column model with a one-dimensional simplified near-anode layer model. Both the electrical and thermal influences from the arc column on arc–anode interaction are considered. Multiple attachments are generated in the fringes of the arc–anode attachment. When the total current is large enough, the multiple anode attachments phenomenon should disappear. This work is based on previous typical works of Trelles and Benilov, and reconfirms the simulation patterns obtained by Trelles.